2023
DOI: 10.5194/esurf-11-117-2023
|View full text |Cite
|
Sign up to set email alerts
|

Multi-sensor monitoring and data integration reveal cyclical destabilization of the Äußeres Hochebenkar rock glacier

Abstract: Abstract. This study investigates rock glacier destabilization based on the results of a unique in situ and remote-sensing-based monitoring network focused on the kinematics of the rock glacier in Äußeres Hochebenkar (Austrian Alps). We consolidate, homogenize, and extend existing time series to generate a comprehensive dataset consisting of 14 digital surface models covering a 68-year time period, as well as in situ measurements of block displacement since the early 1950s. The digital surface models are deriv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Practical examples have already confirmed that RGV derived from UAV-data, i.e. multi-temporal digital orthophotos and/or surface models, compare very well with geodetic point measurements if photos taken are of high spatial resolution [49,51].…”
Section: Geodetic Monitoring Of Rock Glaciersmentioning
confidence: 85%
See 2 more Smart Citations
“…Practical examples have already confirmed that RGV derived from UAV-data, i.e. multi-temporal digital orthophotos and/or surface models, compare very well with geodetic point measurements if photos taken are of high spatial resolution [49,51].…”
Section: Geodetic Monitoring Of Rock Glaciersmentioning
confidence: 85%
“…Since 1951, creep velocity has been measured at this RG by terrestrial geodetic methods and since 2008 by Global Navigation Satellite System (GNSS) technology [69][70][71][72][73]. A06 has the worldwide longest record of RGV data [48,70] although several gaps exist [49,73]. Annual terrestrial geodetic surveys to derive RGV have been included as part of the long-term observation strategy of the Swiss Permafrost Monitoring Network PERMOS since 2008 to complement the measurements of permafrost temperature and changes in ground ice content [74].…”
Section: Geodetic Monitoring Of Rock Glaciersmentioning
confidence: 99%
See 1 more Smart Citation
“…These rock glaciers are a potential outcome of permafrost in nonequilibrium conditions. Increased warming is predicted to boost the degree of activity of rock glaciers and support faster movement of rock glaciers (Hartl et al 2023), increasing the potential for such events, however investigations into this direction in HMA are lacking.…”
Section: Geomorphological Impactsmentioning
confidence: 99%
“…Knowledge on adaptations of high mountain species to slope movements exists already for a long time (Schröter et al, 1926), but relationships between plant traits and movement intensities have rarely been quantified. To achieve this, measurements of mountain plant traits, facilitated by well-standardized methods (Freschet et al, 2021;Pérez-Harguindeguy et al, 2013), could be carried out on slopes with known movement rates increasingly provided by new techniques such as terrestrial laser scanning, uncrewed aerial vehicle (UAV) surveys and InSAR (Hartl et al, 2023;Hendrickx et al, 2020;Rouyet et al, 2021). While extensive plant trait databases exist (Bjorkman et al, 2018a(Bjorkman et al, , 2018bKattge et al, 2011Kattge et al, , 2020Maitner et al, 2018), data availability is often limited for alpine species and many important biomechanical traits, such as root tensile strength or modulus of elasticity, are far from being included routinely in ecological databases.…”
Section: Biogeomorphic Balance Mechanisms: Linking Plant Traits To Sl...mentioning
confidence: 99%